Impacts of season phases and training variables on mental fatigue in real-world elite fencing - Bian, C.; Russell, S.; De Pauw, K.; Ampe, T.; Bogataj, Š.; Roelands, B. (International Journal of Sports Physiology and Performance, 2025)
Purpose: Mental fatigue (MF) is increasingly implicated in elite sports, yet its characteristics and impact in real-world fencing, a highly perceptual-cognitive demanding domain, are underexplored.